KEARIFAN LOKAL VERSUS KELESTARIAN MANGROVE: UPAYA MENJAGA KAWASAN PESISIR KABUPATEN BELITUNG DARI KERUSAKAN - Robert Siburian (Jurnal Masyarakat dan Budaya, 2014)
This paper aims to explain the local wisdom related to ecology of Belitung people. It has existed from generations to generations. There three forms of local wisdom related to ecology, namely dukun kampung, kelekak, and hutan larangan. Although they have that local wisdom, the forest area in Belitung remains damage. It indicates that the local wisdom has not been implemented into their life, particularly in relation to the environment where they live. However, the reality in the forest is not similar to the mangrove plants. Although the local wisdom does not orient to the sea, the mangrove plants is in a very good condition. Analysing that case, this paper focuses on the understanding of Belitung people on mangrove plant related to their local wisdom. Keywords: local wisdom, ecology, mangrove sustainability, coastal area, environmental damage